High‐Performance Biodegradable Energy Storage Devices Enabled by Heterostructured MoO3–MoS2 Composites. Issue 10 (12th December 2022) - Shao, Mingjiao; Sheng, Hongwei; Lin, Liqi; Ma, Hongyun; Wang, Qi; Yuan, Jiao; Zhang, Xuetao; Chen, Gang; Li, Wenquan; Su, Qing; Xie, Erqing; Wang, Jing; et al.
Abstract: Biodegradable implantable devices are of growing interest in biosensors and bioelectronics. One of the key unresolved challenges is the availability of power supply. To enable biodegradable energy‐storage devices, herein, 2D heterostructured MoO3 –MoS2 nanosheet arrays are synthesized on water‐soluble Mo foil, showing a high areal capacitance of 164.38 mF cm −2 (at 0.5 mA cm −2 ). Employing the MoO3 –MoS2 composite as electrodes of a symmetric supercapacitor, an asymmetric Zn‐ion hybrid supercapacitor, and an Mg primary battery are demonstrated. Benefiting from the advantages of MoO3 –MoS2 heterostructure, the Zn‐ion hybrid supercapacitors deliver a high areal capacitance (181.86 mF cm −2 at 0.5 mA cm −2 ) and energy density (30.56 µWh cm −2 ), and the Mg primary batteries provide a stable high output voltage (≈1.6 V) and a long working life in air/liquid environment. All of the used materials exhibit desirable biocompatibility, and these fabricated devices are also fully biodegradable. Demonstration experiments display their potential applications as biodegradable power sources for various electronic devices. Abstract : Based on 2D, heterostructured MoO3 –MoS2 composites, three types of biodegradable energy storage devices are constructed including the symmetric supercapacitor, asymmetric Zn‐ion hybrid supercapacitor, and Mg primary battery. These devices with a well‐designed encapsulation strategy can fully degrade in a body liquid environment after ending their lifetime.